2001
DOI: 10.1001/archpsyc.58.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Sleep Electroencephalogram in Depressed Patients Treated With Phenelzine

Abstract: Antidepressant response to phenelzine treatment does not depend on elimination of REM sleep or inhibition of SWA in non-REM sleep. In depressed patients, REM sleep is regulated independently from non-REM sleep and can be manipulated without altering the dynamics of SWA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…Within the frequency bands showing a significant Treatment effect, rANOVA identified four distinct bands with either a significant effect of Derivation and/or a significant Treatment X Derivation interaction. They were located in the ranges 2.0-3.25 Hz, Hz ( Table 2).As reported in our previous paper, phenelzine treatment was associated with increased tonic EMG activity during sleep (Landolt et al 2001). Spearman rank correlation analysis revealed that the treatment-induced increase of EEG power density in the 19.0-22.25 Hz band in fronto-central and centro-parietal derivations (Table 3) was significantly correlated with the increase of tonic EMG activity (r s ϭ 0.74 and 0.76, respectively, p Ͻ .04; n ϭ 8).…”
supporting
confidence: 69%
See 4 more Smart Citations
“…Within the frequency bands showing a significant Treatment effect, rANOVA identified four distinct bands with either a significant effect of Derivation and/or a significant Treatment X Derivation interaction. They were located in the ranges 2.0-3.25 Hz, Hz ( Table 2).As reported in our previous paper, phenelzine treatment was associated with increased tonic EMG activity during sleep (Landolt et al 2001). Spearman rank correlation analysis revealed that the treatment-induced increase of EEG power density in the 19.0-22.25 Hz band in fronto-central and centro-parietal derivations (Table 3) was significantly correlated with the increase of tonic EMG activity (r s ϭ 0.74 and 0.76, respectively, p Ͻ .04; n ϭ 8).…”
supporting
confidence: 69%
“…We have recently reported that delta power in non-REM sleep was not affected in a central EEG derivation in depressed patients when REM sleep was virtually abolished during treatment with phenelzine (Landolt et al 2001). In view of possible regional differences in sleep regulation, we have now investigated the effect of phenelzine on EEG topography in wakefulness and sleep.…”
Section: A Novel Approach To Investigate the Relationship Between Depmentioning
confidence: 99%
See 3 more Smart Citations